S37 Can the Lung Reverse Remodel? Gene Therapy For Cardiac Failure Alters Pulmonary Gene Expression. (19th November 2012) - Park, JES; Lyon, AR; Hector, L; Griffiths, MJD
Abstract : Introduction: Irreversible alveolar capillary membrane (ACM) remodelling accompanies chronic heart failure (CHF), contributing to dyspnoea, the predominant symptom that limits quality of life in CHF. Gene therapy is aimed at improving myocardial function in CHF. Restoration of Sarco-endoplasmic reticulum calcium ATPase (SERCA2a) gene expression in animal models of CHF restores haemodynamic parameters towards normal. The lungs are the direct upstream target of raised left atrial pressure and hence pulmonary venous hypertension. We hypothesised that mechanical strain at the pulmonary micro vasculature associated with PVH up-regulates mediators leading to pulmonary inflammation and ACM remodelling. We have previously shown that gene expression of monocyte chemoattractant protein (MCP)-1, interleukin(IL)-6, endothelin (ET)-1, endothelin receptors (ETR) A and B, and endothelial converting enzyme (ECE) are altered in the lungs of Sprague-Dawley rats at 16 weeks after left coronary artery ligation. We now sought to determine the effect of SERCA2a gene therapy on gene expression of these mediators in the lung. Methods: Gene expression of components of the ET-1 pathway, MCP-1 and IL-6 were investigated in whole lungs of rats at 16 weeks after LCA, at 16 weeks post LCA with tail vein injection of adeno-associated viral (AAV) gene transfer of SERCA2a at 12 weeks post LCA, or sham procedure(n=5 in each group). Lungs were snap frozen in liquid nitrogen, RNA extracted using a modified Trizol and RN easy protocol and gene expression determined in reverse transcribed cDNA by qPCR. Results: Expression of ET-1, ETAR, MCP-1 and IL-6 genes were elevated in heart failure animals and reduced to or towards normal in SERCA2a treated animals. In heart failure animals there was a trend towards reduced ETRB expression which was significantly improved by SERCA2a gene therapy (figure 1 ). ECE gene expression was not altered by LCA or gene therapy. Conclusion: SERCA2a gene therapy directed at the myocardium in heart failure also affects gene expression in the lungs of CHF animals. This may provide therapeutic benefit to the lungs in addition, reducing inflammation and stimuli associated with structural and vascular remodelling.